MORPHOMETRIC CHARACTERISTICS OF THE RAT SMALL BRONCHI IN CONSUMPTION OF THE COMPLEX OF FOOD ADDITIVES - Yeroshenko, G.А.; Donets, І.М.; Shevchenko, К.V.; Lysachenko, О.D.; Solod, А.V.; Vatsenko, A.V.; Ulanovska-Tsyba, N.A. (World of Medicine and Biology, 2022)
The paper presents the data of the morphometric study of the small bronchi of the lungs of rats under the complex effect of food additives. It has been established that consumption of the complex of food additives leads to a change in the morphometric parameters of the structural components of the small bronchi of the rat lungs, which at the early stages is manifested by a significant decrease in the morphometric parameters of the outer diameter and lumen with a significant increase in the height of the epitheliocytes in the small bronchi of all orders due to the primary endogenous impact of the components of the food additive complex, which is associated with spasm of the exchange blood vessels and the progressive phenomena of hypoxia. Subsequently, the impact of the alterative factor, which prevails over the protective mechanisms of the body, is manifested by the development of bronchospasm in the small bronchi of the 3rd order, the appearance of inflammatory infiltration in the bronchial walls and the formation of bronchial hyperreactivity, which is characteristic of the development of diseases of the respiratory system, including asthma.
Keywords: rats; lungs; small bronchus; monosodium glutamate; sodium nitrite; Ponceau-4R; morphometric study